Recurrent erythema multiforme after alcohol ingestion in a patient receiving ciprofloxacin: a case report. - Lagoudianakis, Emmanuel; Pappas, Apostolos; Koronakis, Nikolaos; Dallianoudis, Ioannis; Kotzadimitriou, Katerina; Chrysikos, John; Koukoutsis, Ilias; Antonakis, Pantelis; Keramidaris, Dimitrios; Manouras, Andreas (Cases J, 2009)
The incidence of cutaneous adverse reactions to quinolones is low; moreover their development in patients with concomitant alcohol consumption is a phenomenon that has been scarcely reported. We present a case of 46-year-old male who developed erythema multiforme after ingestion of alcohol, while being treated with ciprofloxacin. The lesion was self-limiting and abstinence from alcohol permitted the completion of the course of therapy without any other adverse reaction.